Re-adaptation of malay vernacular architecture thermal comfort elements : towards sustainable design in Malaysia. (a literature review) / Nur Hidayahtuljamilah Ramli ... [et al.] - Ramli, Nur Hidayahtuljamilah; Kassim, Norhayati; Mohd. Taib, Zafrullah; Masri, Mawar (2012)
Malay vernacular architecture has been designed with perfect solution to meet thermal comfort of the occupants. The orientation of the house, plenty of windows and openings, roof design and multilevel of floors are part the elements that help them to gain the thermal comfort for occupant’s lives. Bowadays, indoor environment influenced the occupant’s physical and mental health. The practical solutions of the vernacular characteristic in design have caused present designers to re-evaluate their design approach into finding the design solutions to achieve sustainable design.Therefore, in building a good design, ideas are re-adapted from Malay vernacular architecture thermal comfort element into modern building. Re-adaption is one of the design solutions considered but to what extent may the vernacular architecture be adapted to contemporary buildings in order to create a better interior environment for the occupants?The research will use case study and ethnographic observations study whereby the researcher becomes a participant during the process.However, this paper is aimed to review the literature in identifying the relationship between the designs of the Malay vernacular building components to the local climate’s context.The research is intended to change future designers approach towards designing contemporary buildings so that they are more sustainable.